ANALISIS RASIO KEUANGAN DALAM MEMPREDIKSI PERTUMBUHAN LABA PADA BPR MILIK PEMDA KABUPATEN KOTA JATENG DIY PERIODE 2011-2012 - Riswati, 10.05.52.0012; Masdjojo, Gregorius N. (Students Journal of Accounting and Banking, 2014)
This study aims to determine the financial ratio analysis to predict profit growt in local government owned Rural Bank district of Central Java DIY on the periods 2011-2012. Variabel independent in this study consists of the Capital Adequacy Ratio (CAR), Non Performing Loans (NPL), Net Interest Margin (NIM), Operational Efficiency (BOPO), Liquidity (LDR). Dependent variable in this research is earnings growth. The sample used in this study is 28 banks PD BPR Java and PD BPR DIY for 2 periods (2011-2012). Sample taken using purposive sampling. Methods of analysis used in this study is the method of multiple regression analysis. The results of this study indicate that the variable CAR had no effect on earning growth, BOPO effect on earning growth, NIM effect on earning growth, NPL has no effect on earnings growth, and LDR has no earning growth.Keywords: CAR, BOPO, LDR, NPL, NIM, Â Profit growthÂ